The Rhythmotron. - Taylor, John R.; Milne, Andrew J. (Leonardo Music Journal, 2019)
This paper describes the Rhythmotron: a percussion-centered robotic orchestrion, commissioned for the CoLABS festival in Sydney in 2017. The authors describe how they electronically reimagined the mechanical components of a cylinder piano by using a variant of the XronoMorph software, and they consider the synergy between algorithmically generated rhythms in a digital environment alongside its analogous mechanical counterpart. The authors detail the idiosyncratic behaviors of linear actuators when used to power drumming robots, and they discuss the aesthetic implications of the Rhythmotron.